Abiraterone acetate versus docetaxel for metastatic castration-resistant prostate cancer: a cohort study within the French nationwide claims database. Issue 9 (2nd September 2022) - Thurin, Nicolas H.; Rouyer, Magali; Jové, Jérémy; Gross-Goupil, Marine; Haaser, Thibaud; Rébillard, Xavier; Soulié, Michel; de Pouvourville, Gérard; Capone, Camille; Bazil, Marie-Laure; Messaoudi, Fatiha; Lamarque, Stéphanie; et al.
ABSTRACT: Objectives: To conduct the direct comparison of abiraterone acetate and docetaxel for first-line treatment of metastatic castration-resistant prostate cancer (mCRPC) in real-life settings. Methods: Data were extracted from the French nationwide claims database (SNDS) on all men aged ≥40 years starting first-line treatment with abiraterone acetate or docetaxel for mCRPC in 2014. A high-dimensional propensity score including 100 baseline characteristics was used to match patients of both groups and form two comparative cohorts. Three-year overall survival and treatment discontinuation-free survival were determined using Kaplan–Meier analysis. Results: In 2014, 2, 444 patients started abiraterone for treatment of mCRPC and 1, 214 started docetaxel. After trimming and matching, 716 patients were available in each group. Median overall survival tended to be longer in the abiraterone acetate cohort (23.8 months, 95% confidence interval = [21.5; 26.0]) than in the docetaxel cohort (20.3 [18.4; 21.6] months). Survival at 36 months was 34.6% for abiraterone acetate and 27.9% for docetaxel ( p = 0.0027). Treatment discontinuation-free median was longer in the abiraterone acetate cohort compared to the docetaxel cohort (10.8 [10.1; 11.7] versus 7.4 [7.0; 8.0] months). Conclusion: The findings underline the interest of oral abiraterone acetate over intravenous docetaxel as the first-line treatment option in mCRPC.